ORGANIZATIONAL ECONOMIC MANAGEMENT MECHANISM AND DEVELOPMENT STRATEGY FOR THE CHEMICAL AND PETROCHEMICAL SECTOR OF NIGERIA - T. T. Titus; T. Titus (Вестник университета)
Аnnotation. In this article the organizational mechanism of management of economy and the strategy of development for chemical and petrochemical sector of Nigeria is analyzed. To eq implement запасов the optimal development eq нечетко strategy экспорт of the enterprise, directions eq storage were proposed for improving eq крайне long-term нигерии contracts eq between южной enterprises of related eq сегментах business против sectors, namely the eq среди practice called «Vertical eq значительно Integration создав». The authors eq analyze природных Mechanisms of vertical eq вызвать integration storage, as a strategy for the development of the eq рынок petrochemical industry, which eq промышленности will будущие allow to eq minimize связи costs and increase the eq значительно competitiveness айте of both the chemical and eq которые petrochemical industry and the industry as a eq которые whole лидером.